1997
DOI: 10.1007/s002280050240
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-psychiatric effects of antimalarials

Abstract: Insomnia was more commonly encountered during use of mefloquine than proguanil or during non-use of antimalarials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…Two studies have employed a validated symptom measure, the POMS. One of these was not randomized, and found no differences between mefloquine, proguanil or no drug [115]. However, the single randomized study using the POMS reported elevated scores in mefloquine- compared to chloroquine-treated patients [116].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies have employed a validated symptom measure, the POMS. One of these was not randomized, and found no differences between mefloquine, proguanil or no drug [115]. However, the single randomized study using the POMS reported elevated scores in mefloquine- compared to chloroquine-treated patients [116].…”
Section: Resultsmentioning
confidence: 99%
“…Two types of neuropsychiatric adverse events have been attributed to the use of mefloquine: (1) a sensation of dizziness, dysphoria, light-headedness and difficulty in concentrating which occurs within 6 h after intake and usually resolves during the following days; (2) acute psychosis with agitation or depression, occurring in the second week after starting prophylaxis [6]. In a previous study, we found that women in particular developed insomnia on mefloquine [7]. Other studies also found more neuropsychiatric effects in women than in men [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Compliance with quinine is challenging, especially in the 7-to 10-day dosing regimens commonly used for pregnant women and children in Southeast Asia. Mefloquine remains efficacious in most areas of the world but is associated with stillbirth in pregnancy (13), and concerns about neuropsychiatric reactions (19) may limit its use. Artesunate requires 5-to 7-day treatment regimens to achieve acceptable cure rates, and it is therefore usually combined with mefloquine (23).…”
mentioning
confidence: 99%